Person–environment interactions among residents of Oxford Houses. (June 2013) - Beasley, Christopher R.; Jason, Leonard A.; Miller, Steven A.; Stevens, Ed; Ferrari, Joseph R.
<x xml:space="preserve">Abstract</x> The continued struggle of addiction recovery support systems suggest that the paradigm of this field needs to continue its evolution, which has increasingly emphasized environments. Field Theory suggests that the products of individual and environmental characteristics be considered rather than a summation of the two. This study examined such interactions in Oxford Houses, a network of democratic, and self-governed addiction recovery homes. This study examined sobriety in experienced houses (average length of residency > six months) compared to less experienced houses (average length of residency ≤ six months) in relation to individual resident characteristics (age, length of residence in an Oxford House, and referral from the criminal justice system). Using multilevel modeling, findings indicated that older residents living in an experienced Oxford Houses were more likely to remain abstinent over time than those in inexperienced homes. Additionally, for inexperienced houses, residents who had been in the Oxford House for a longer period had a higher the probability of abstinence than those that had been in the house for a shorter period of time. Finally, legal referral was related to a lower probability of one-year abstinence but only for those in experienced homes. These types of person–environment interactions point to the need for more research to better understand how person variables interact with environmental variables in the processes of recovery and adaptation to settings, as well as for treatment professionals' consideration of both person and environment when making recovery home referrals.